Myeloid Cell Infiltration Correlates With Prognosis in Cholangiocarcinoma and Varies Based on Tumor Location. Issue 7 (September 2021) - Kunk, Paul R.; Dougherty, Sean C.; Lynch, Kevin; Whitehair, Rachel; Meneveau, Max; Obeid, Joseph M.; Winters, Kevin; Ju, Jennifer Y.; Stelow, Edward B.; Bauer, Todd W.; Slingluff, Craig L.; Rahma, Osama E.
Abstract : Cholangiocarcinoma (CC) is an uncommon malignancy with increasing incidence and dismal prognosis. We conducted a comprehensive analysis of the CC tumor immune microenvironment (TIME) based on tumor location to identify therapeutic targets. We hypothesized that the TIME of CC would vary by primary tumor location and that high tumor infiltration by CD8 + T cells and low infiltration by M2 macrophages would be associated with improved survival. A retrospective analysis was conducted of 99 CC tumor samples surgically resected between 2000 and 2014. Tissue microarrays were constructed from each tumor and stained by immunohistochemistry for 24 markers of immune cells, immune activation or inhibition, programmed cell death-ligand 1, and mesothelin. Most tumors were amply infiltrated with by CD4 +, CD8 +, and FoxP3 + T cells, as well as by myeloid cells. Mesothelin expression ≥1+ by immunohistochemistry was found in 68% of tumors. We identified higher densities of M1 macrophages in primary distal extrahepatic CC, as well as metastatic lesions. Mesothelin expression was also significantly higher in distal extrahepatic CC. There was no association with survival of infiltration by CD4 +, CD8 +, or FoxP3 + T cells, mesothelin expression, or programmed cell death-ligand 1 percentage expression, however, high CD14 + myeloid cells and high CD163 + M2 macrophages were associated with worse survival. In conclusion, the CC TIME is a heterogenous milieu highly infiltrated by innate and adaptive immune cells, which differs based on primary tumor location and between primary tumors and metastatic lesions. The correlation of intratumoral M2 macrophages and myeloid cells with a worse prognosis may suggest promising immunotherapeutic targets in CC. Abstract : Supplemental Digital Content is available in the text.